2020
DOI: 10.3390/en13195200
|View full text |Cite
|
Sign up to set email alerts
|

Methane Hydrate Formation and Dissociation in Sand Media: Effect of Water Saturation, Gas Flowrate and Particle Size

Abstract: Assessing the influence of key parameters governing the formation of hydrates and determining the capacity of the latter to store gaseous molecules is needed to improve our understanding of the role of natural gas hydrates in the oceanic methane cycle. Such knowledge will also support the development of new industrial processes and technologies such as those related to thermal energy storage. In this study, high-pressure laboratory methane hydrate formation and dissociation experiments were carried out in a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…Figure 5a summarize the measured induction times for the first series of experiments performed at constant injected water volume in sand and clay/sand mixtures (experiments 1_1 to 5_5 in Table 4). The average induction time for hydrate formation within the sand is 50 ± 6 min, which is close to the value of 53 ± 5 min obtained by Benmesbah et al (2020) in a previous study using the same apparatus and operating conditions.…”
Section: Influence Of Clay Content On Induction Timesupporting
confidence: 87%
“…Figure 5a summarize the measured induction times for the first series of experiments performed at constant injected water volume in sand and clay/sand mixtures (experiments 1_1 to 5_5 in Table 4). The average induction time for hydrate formation within the sand is 50 ± 6 min, which is close to the value of 53 ± 5 min obtained by Benmesbah et al (2020) in a previous study using the same apparatus and operating conditions.…”
Section: Influence Of Clay Content On Induction Timesupporting
confidence: 87%
“…According to the literature, particle size is one of key factors affecting the gas hydrates formation in a porous media [40,41]. It was shown [42] that media with a particle size of fewer than 4 µm are characterized by a significant shift in the equilibrium conditions of hydrate formation towards lower temperatures and higher pressure.…”
Section: Introductionmentioning
confidence: 99%
“…According to studies [43,44], the rate of hydrate formation is higher in quartz sand with smaller particles. Another relevant characteristic for hydrate formation in porous sediments is water saturation [35,40,41,45]. It was shown that an increase in water saturation resulted in a decrease in water to hydrate conversion while the addition of sodium dodecyl sulfate removing this restriction.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, recent efforts have focused on improving the kinetics of hydrate formation through methods that enhance contact between the guest and the water molecules. A wide range of porous media has been investigated, including metal-organic frameworks (MOFs) [37], silica sands [38][39][40], silica gels [39,41], superabsorbent polymers (SAP) [42][43][44], glass beads [45], clay [46], activated carbon [47,48], nanotubes [49,50], and biological porous materials [51]. If we disregard the impact of porous media on the phase equilibrium of gas hydrates, it is commonly believed that such media can provide a greater number of nucleation sites [52,53], increase the gas-liquid contact areas [54], thus promoting hydrate formation kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of factors, such as water saturation, gas flow rate, particle size, and the morphology of porous media on CO2 hydrate and methane hydrate formation and dissociation processes, has been extensively investigated in References [39] and [40], respectively. It is disappointing that the particle size of porous media has been found to have an opposite effect on hydrate formation kinetics and gas storage capacity [56].…”
Section: Introductionmentioning
confidence: 99%